Kekerasan Seksual Terhadap Warga Sipil Dalam Konflik Antara Rusia Dan Ukraina Ditinjau Dari Hukum Humaniter Internasional - Ariwati, Setya Andhini; Tukan, Elisabeth N S B (Artemis Law Journal, 2024)
Sexual violence committed by Russian soldiers during the conflict between Russia and Ukraine was violates the provisions of international humanitarian law, particularly the Fourth Geneva Convention on the protection of civilians during war time. This study aims to understand the regulations on the protection of civilians from sexual violence according to the Fourth Geneva Convention and its two additional protocols and examine the enforcement of laws against Russian soldiers who committed sexual violence against civilians during the Russia-Ukraine conflict.The research method used in this study is normative legal research, which involves reviewing books on rules and laws conducted in a library setting.The results of this study indicate that, the attacks by Russian soldiers on civilians in the Russia-Ukraine conflict have violated articles of the Fourth Geneva Convention and its two additional protocols, such as Articles 27-34 of the Fourth Geneva Convention of 1949; Article 51 of Additional Protocol I of 1977; Articles 13-18 of Additional Protocol II of 1977. Various acts of sexual violence committed by Russian soldiers against civilians in the Russia-Ukraine conflict have violated Article 27, paragraph two of the Fourth Geneva Convention of 1949; Article 75, paragraph (2) point a and paragraph (5) of Additional Protocol I of 1977; Article 4 paragraph (2) letter e and Article 5 of Additional Protocol II of 1977 and after thoroughly evaluating and eliminating various judicial mechanisms, the most viable approach to legally address the acts of sexual violence perpetrated by Russian soldiers against civilians is to pursue enforcement through an hybrid tribunal.